Impact of pH on the physicochemical and rheological properties of mung bean (Vigna radiata L.) protein. (December 2021) - Liu, Fen-Fang; Li, Ying-Qiu; Wang, Chen-Ying; Zhao, Xiang-Zhong; Liang, Yan; He, Jin-Xing; Mo, Hai-Zhen
Graphical abstract: Highlights: Mung bean protein (MBP) contained mainly six bands 64, 62, 48, 32, 25, 23 kDa. Abundant hydrophobic amino acids of MBP contributed to high thermostability at pH 7.0. MBP had a looser structure in alkaline environment than acid environment. More than 130 mg/mL MBP formed self-supporting gels at pH 7.0 and 9.0. MBP had good physicochemical and functional properties in alkaline environment. Abstract: This study aimed to investigate the structural characteristics and physicochemical properties of mung bean protein (MBP) at different pH levels. Structures and physicochemical properties were evaluated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, circular dichroism, ultraviolet visible and fluorescence spectrophotometry, differential scanning calorimetry, etc. MBP contained six bands of 64, 62, 48, 32, 25 and 23 kDa, among which the 64, 48 and 32 kDa bands consisted of glycoproteins. The β-sheets and random coils of MBP had structures close to double α-helices and β-turns at pH 3.0, 7.0 and 9.0. MBP in an alkaline environment had higher solubility and free sulfhydryl contents, smaller particle sizes, and lower surface hydrophobicity. Rheological analysis showed that MBP at pH 3.0, 5.0, 7.0 and 9.0 exhibited shear-thinning pseudoplastic fluids. A higher shear stress was needed to initiate flow at pH 5.0 than at pH 3.0, 7.0 or 9.0. MBP (130 mg/mL) formed self-supporting gels at pH 7.0 and 9.0. MBP had good foaming capacity (125.00 %), emulsion activity index (117.05 m 2 /g) and emulsion stability index (20.86 min) in alkaline environment. These results provide fundamental information about MBP for use in neutral and alkaline environments as a functional food ingredient.